Transparent adhesive sheet and transparent adhesive sheet having release material
Patent Information
- Application Number
- JP2024228454
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-03-26
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-02-14
AI Technical Summary
【0008】 本透明接着シートによると、厚さについて均一性高く作製されうるとともに流動化しにくいシートの形態で、接合対象物間に接着材料を供給することが可能である(流動化しにくい接着材料は、接合対象物間の接合過程において当該接合対象物間からのはみ出しを生じにくい)。したがって、本透明接着シートによると、液状接着剤による場合よりも、接合対象物である光学式センサと透明カバー部材との間を厚さの均一性の高い接着剤層でもって接合することが可能である。光学式センサと透明カバー部材との間を厚さの均一性の高い接着剤層によって接合可能であることは、透明カバー部材に対して光学式センサを姿勢精度よく接合するうえで好適であり、ひいては、当該光学式センサが組み込まれるデバイスを歩留まりよく製造するうえで好適である。
Smart Images

Figure 2025036544000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a transparent adhesive sheet and a transparent adhesive sheet with release materials on both sides. [Background technology]
[0002] Transparent adhesives are used as a means for joining parts together in various devices such as liquid crystal display devices, etc. Such transparent adhesives are described in, for example, the following Patent Documents 1 to 3. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-140408 A [Patent Document 2] Special Publication No. 2016-505690 [Patent Document 3] JP 2017-66294 A Summary of the Invention [Problem to be solved by the invention]
[0004] In devices equipped with optical sensors, the optical sensors are often assembled in such a manner that their detection surface faces or abuts against a transparent cover member such as glass. In such devices equipped with optical sensors, when a transparent liquid adhesive is used as a means for joining the transparent cover member and the optical sensor, the optical sensor may not be joined to the transparent cover member with good posture accuracy. This is because the thickness of the liquid adhesive may be non-uniform when it is applied or supplied onto the transparent cover member or the optical sensor, and the adhesive may overflow from between the cover member and the optical sensor, which are the objects to be joined, during the joining process. Low posture accuracy in joining or attaching the optical sensor may cause a decrease in yield in the manufacture of devices in which the optical sensor is incorporated.
[0005] On the other hand, conventional sheet-type adhesives, as a means of bonding between a transparent cover member and an optical sensor, may not be able to achieve a transparency sufficient to ensure effective detection sensitivity of the optical sensor within the device while ensuring bonding reliability.
[0006] The present invention was devised in light of the above circumstances, and its purpose is to provide a transparent adhesive sheet and a transparent adhesive sheet with a release material that can be used as a bonding material between the detection surface of an optical sensor and a transparent cover member, which is suitable for manufacturing devices equipped with an optical sensor with good yield and for ensuring the detection sensitivity of the sensor. [Means for solving the problem]
[0007] According to a first aspect of the present invention, there is provided a transparent adhesive sheet, which is made of a thermosetting adhesive material and has a transmittance (light transmittance) of 85% or more in the wavelength range of 450 to 1200 nm when heat-cured by heating at 150°C for 1 hour.
[0008] According to the transparent adhesive sheet, it is possible to supply an adhesive material between objects to be joined in the form of a sheet that can be produced with high uniformity in thickness and is difficult to flow (an adhesive material that is difficult to flow is less likely to spill out from between the objects to be joined during the joining process). Therefore, according to the transparent adhesive sheet, it is possible to join the objects to be joined, that is, the optical sensor and the transparent cover member, with an adhesive layer having a high uniformity of thickness compared to the case of using a liquid adhesive. Being able to join the optical sensor and the transparent cover member with an adhesive layer having a high uniformity of thickness is suitable for joining the optical sensor to the transparent cover member with good posture accuracy, and is also suitable for manufacturing devices incorporating the optical sensor with good yield.
[0009] In addition, as described above, the transparent adhesive sheet has a transmittance of 85% or more in the wavelength range of 450 to 1200 nm when thermally cured by heating at 150°C for 1 hour. The transmittance is preferably 87% or more, and more preferably 90% or more. The transparent adhesive sheet has such a light transmittance over the wavelength range from visible light to near infrared light after thermal curing, making it suitable for use as a bonding material between the detection surface of an optical sensor and a transparent cover member to ensure the effective detection sensitivity of the optical sensor in a device.
[0010] As described above, the present transparent adhesive sheet is suitable for use as a bonding material between the detection surface of an optical sensor and a transparent cover member, for manufacturing devices equipped with an optical sensor with good yield, and for ensuring the detection sensitivity of the sensor.
[0011] In the present transparent adhesive sheet, in a heat-cured state by heating at 150°C for 1 hour, the ratio (first ratio) of the transmittance at a wavelength of 450 nm after the moisture absorption test under the conditions (first conditions) of 30°C, relative humidity of 70%, and 200 hours to the transmittance at a wavelength of 450 nm before the moisture absorption test is preferably 0.9 or more, more preferably 0.92 or more, and more preferably 0.94 or more. The configuration in which the decrease in the transmittance of the transparent adhesive sheet due to the moisture absorption test under the first conditions is so small is suitable for ensuring the above-mentioned sensor detection sensitivity. In addition, the first ratio is, for example, 1 or less.
[0012] In the present transparent adhesive sheet, in a heat-cured state by heating at 150°C for 1 hour, the ratio (second ratio) of the transmittance at a wavelength of 450 nm after the heating test at 260°C for 5 minutes (second condition) to the transmittance at a wavelength of 450 nm before the heating test is preferably 0.9 or more, more preferably 0.92 or more, and more preferably 0.94 or more. The configuration in which the decrease in the transmittance of the transparent adhesive sheet due to the heating test under the second condition is so small is suitable for ensuring the above-mentioned sensor detection sensitivity. In addition, the second ratio is, for example, 1 or less.
[0013] The viscosity of the present transparent adhesive sheet or the adhesive composition constituting it at 120° C. is preferably 1 to 30 kPa·s, more preferably 3 to 30 kPa·s, more preferably 4 to 27 kPa·s, and more preferably 5 to 25 kPa·s. Such a configuration is suitable for ensuring good wettability of the present transparent adhesive sheet to the object to be joined.
[0014] The present transparent adhesive sheet has a storage modulus of preferably 0.5 to 50 MPa, more preferably 0.6 to 45 MPa, and more preferably 0.7 to 40 MPa at 250° C. in a heat-cured state after heating for 1 hour at 150° C. Such a configuration is suitable for ensuring the adhesive strength of the transparent adhesive sheet between objects to be joined after curing, and is therefore suitable for ensuring the adhesive reliability between objects to be joined by the present transparent adhesive sheet.
[0015] The transparent adhesive sheet, in a heat-cured state after heating at 150° C. for 1 hour, preferably exhibits a weight loss rate of 1.5% or less, more preferably 1.2% or less at 300° C., as measured by thermogravimetry under conditions of a nitrogen atmosphere, a heating rate of 10° C. / min, and a heating range of 23 to 300° C. Such a configuration is suitable for ensuring the heat resistance of the transparent adhesive sheet, and therefore is suitable for ensuring the bonding reliability of objects bonded by the transparent adhesive sheet.
[0016] The transparent adhesive sheet exhibits a peel adhesion strength of preferably 1 N / 10 mm or more, more preferably 1.5 N / 10 mm or more, against a flat glass surface in a peel test under conditions of 23° C., a peel angle of 180°, and a peel speed of 30 mm / min. Such a configuration is suitable for ensuring the adhesive strength of the transparent adhesive sheet to the object to be joined.
[0017] The present transparent adhesive sheet has a ratio (third ratio) of the glass shear adhesive strength after a moisture absorption test under conditions (third conditions) of 40°C, 95% relative humidity, and 120 hours in the glass-adhered state to the glass shear adhesive strength in the state (glass-adhered state) after heating at 150°C for 1 hour, which is preferably 0.6 or more, more preferably 0.7 or more, and more preferably 0.75 or more. The configuration in which the decrease in the glass shear adhesive strength of the transparent adhesive sheet due to the moisture absorption test under the third conditions is so small is suitable for ensuring the bonding reliability of the object to be bonded by the present transparent adhesive sheet. The third ratio is, for example, 1.5 or less.
[0018] The transparent adhesive sheet preferably has a refractive index of 1.4 to 1.5, and more preferably 1.42 to 1.48 at a wavelength of 633 nm in a heat-cured state after heating for 1 hour at 150° C. Such a configuration is suitable for ensuring the above-mentioned sensor detection sensitivity.
[0019] The transparent adhesive sheet preferably contains an acrylic resin. The acrylic resin preferably has a nitrile group and preferably has an epoxy group. The ratio of the acrylic resin in the organic components contained in the transparent adhesive sheet is preferably 95% by mass or more, more preferably 97% by mass or more. In addition, the transparent adhesive sheet preferably does not contain or substantially does not contain an epoxy resin and / or a phenol resin. These configurations are suitable for achieving a high degree of transparency in the transparent adhesive sheet.
[0020] When the present transparent adhesive sheet contains an acrylic resin such as a nitrile group-containing acrylic resin, the average molecular weight of the acrylic resin is preferably 400,000 or less, more preferably 350,000 or less. Such a configuration is suitable for realizing the above-mentioned preferred configuration regarding the viscosity of the present transparent adhesive sheet.
[0021] The transparent adhesive sheet preferably contains a filler having an average particle size of 5 to 100 nm. The content of the filler in the transparent adhesive sheet is preferably 5 to 45 mass%, more preferably 6 to 40 mass%, and more preferably 7 to 35 mass%. These configurations are suitable for ensuring the heat resistance of the transparent adhesive sheet, and therefore suitable for ensuring the bonding reliability of the objects bonded by the transparent adhesive sheet. In addition, these configurations also contribute to ensuring the transparency of the transparent adhesive sheet.
[0022] The present transparent adhesive sheet preferably contains a phosphorus-based antioxidant. The content of the phosphorus-based antioxidant in the present transparent adhesive sheet is preferably 0.1 to 2 mass %, more preferably 0.3 to 1.5 mass %. These configurations are suitable for preventing and suppressing oxidation of the components contained in the present transparent adhesive sheet, and therefore suitable for preventing and suppressing a decrease in transparency due to the oxidation.
[0023] The present transparent adhesive sheet preferably contains an imidazole-based curing agent. The content of the imidazole-based curing agent in the present transparent adhesive sheet is preferably 0.1 to 2 mass %, more preferably 0.2 to 1.5 mass %. Such a configuration is suitable for achieving both the curability and storage stability of the present transparent adhesive sheet.
[0024] According to a second aspect of the present invention, there is provided a transparent adhesive sheet with a release material. This transparent adhesive sheet with a release material has a laminated structure including a first release material, a second release material, and the transparent adhesive sheet according to the first aspect between these release materials. The transparent adhesive sheet according to the first aspect of the present invention may thus be accompanied by a release material.
[0025] In the present transparent adhesive sheet with a release material, the first release material preferably has a thickness of 38 μm or more, and the second release material preferably has a thickness of 25 μm or more. The ratio of the thickness of the first release material to the thickness of the second release material is preferably 0.2 to 1.8, more preferably 0.22 to 1.6, and even more preferably 0.3 to 1.55. Such a configuration is preferable from the viewpoint of workability when handling the present transparent adhesive sheet with a release material. Specifically, the same configuration is suitable for preventing or suppressing the occurrence of wrinkles or folds in the transparent adhesive sheet when peeling the first release material from the transparent adhesive sheet (which has the second release material on the side opposite to the first release material) in the present transparent adhesive sheet with a release material.
[0026] In this transparent adhesive sheet with a release material, the first release material exhibits a first peel adhesion force of preferably 0.01 N / 100 mm or more, more preferably 0.015 N / 100 mm or more, in a peel test under the conditions of 100°C, a peel angle of 180°, and a peel speed of 300 mm / min, and the second release material exhibits a second peel adhesion force of preferably 0.04 N / 100 mm or more, in a peel test under the conditions of 100°C, a peel angle of 180°, and a peel speed of 300 mm / min, in a peel test under the conditions of 100°C, a peel angle of 180°, and a peel speed of 300 mm / min, in a peel test. The ratio of the first peel adhesion force to the second peel adhesion force is preferably 0.01 to 0.75, more preferably 0.02 to 0.7. These configurations are preferable from the viewpoint of a balance between sufficient adhesion of each release material (which is often peeled off separately from the transparent adhesive sheet at different stages) to the transparent adhesive sheet during handling of this transparent adhesive sheet with a release material, and appropriate releasability of both release materials from the transparent adhesive sheet.
[0027] In the present transparent adhesive sheet with release material, the second release material is preferably a dicing tape having a laminated structure including a substrate and a pressure-sensitive adhesive layer, and the transparent adhesive sheet is releasably adhered to the pressure-sensitive adhesive layer of the dicing tape. Thus, the transparent adhesive sheet according to the first aspect of the present invention may be configured as a transparent adhesive sheet with dicing tape.
[0028] The adhesive layer of the dicing tape preferably contains an acrylic resin having a 2-ethylhexyl group. The thickness of the adhesive layer is preferably 5 to 40 μm, more preferably 10 to 30 μm. Such a configuration is suitable for realizing high adhesion between the adhesive layer of the dicing tape and the transparent adhesive sheet.
[0029] According to a third aspect of the present invention, there is provided a bonding method. In this bonding method, the above-mentioned transparent adhesive sheet according to the first aspect of the present invention is used to bond a glass member to another member. In this manner, the transparent adhesive sheet according to the first aspect of the present invention and the transparent adhesive sheet with release material according to the second aspect of the present invention may be used for bonding between a glass member and another member.
[0030] According to a fourth aspect of the present invention, there is provided another bonding method. In this bonding method, the transparent adhesive sheet according to the first aspect of the present invention is used to bond a transparent resin member having a transmittance of 80% or more at a wavelength of 500 nm to another member. In this manner, the transparent adhesive sheet according to the first aspect of the present invention and the transparent adhesive sheet with a release material according to the second aspect of the present invention may be used to bond between the transparent resin member and another member.
[0031] According to a fifth aspect of the present invention, another bonding method is provided. This bonding method includes a step of laminating the transparent adhesive sheet according to the first aspect of the present invention to a member, a step of singulating the member together with the transparent adhesive sheet to obtain a member piece with the transparent adhesive sheet, and a step of bonding the member piece with the transparent adhesive sheet to another member via the transparent adhesive sheet. According to this bonding method, a member piece with a transparent adhesive sheet (one of the objects to be bonded) can be efficiently obtained. Therefore, this bonding method is suitable for improving the efficiency of the work and process of bonding objects to be bonded. [Brief description of the drawings]
[0032] [Figure 1] 1 is a schematic cross-sectional view of a transparent adhesive sheet with a release material according to one embodiment of the present invention. [Diagram 2] 1 is a cross-sectional view showing bonding between components using a transparent adhesive sheet according to one embodiment of the present invention. [Diagram 3] 1 is a schematic cross-sectional view of a transparent adhesive sheet with a release material according to one embodiment of the present invention. [Figure 4] 4 shows some steps in a bonding method in which the transparent adhesive sheet with a release material shown in FIG. 3 is used. [Diagram 5] 4 shows some steps in a bonding method in which the transparent adhesive sheet with a release material shown in FIG. 3 is used. [Figure 6] 4 shows some steps in a bonding method in which the transparent adhesive sheet with a release material shown in FIG. 3 is used. [Figure 7] 4 shows some steps in a bonding method in which the transparent adhesive sheet with a release material shown in FIG. 3 is used. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] 1 is a schematic cross-sectional view of a transparent adhesive sheet X1 with a release material according to one embodiment of the present invention. The transparent adhesive sheet X1 with a release material has a laminated structure including a transparent adhesive sheet 10 according to one embodiment of the present invention and release liners R1 and R2, which are release materials.
[0034] The transparent adhesive sheet 10 is a transparent sheet-like adhesive having thermosetting properties, and can be used, for example, as an adhesive for bonding between a detection surface of an optical sensor and a transparent cover member in the manufacturing process of a device equipped with an optical sensor. The transparent adhesive sheet 10 may have a composition (first composition) containing a thermosetting resin and a thermoplastic resin as resin components, or a composition (second composition) containing a thermoplastic resin with a thermosetting functional group that can react with a curing agent to form a bond as a resin component. When the transparent adhesive sheet 10 has the second composition, the transparent adhesive sheet 10 does not need to further contain a thermosetting resin.
[0035] When the transparent adhesive sheet 10 has the first composition, examples of the thermosetting resin include epoxy resin, phenol resin, amino resin, unsaturated polyester resin, polyurethane resin, silicone resin, and thermosetting polyimide resin. The transparent adhesive sheet 10 may contain one type of thermosetting resin or two or more types of thermosetting resin.
[0036] Examples of the epoxy resin include bifunctional epoxy resins and polyfunctional epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, brominated bisphenol A type epoxy resin, hydrogenated bisphenol A type epoxy resin, bisphenol AF type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, fluorene type epoxy resin, phenol novolac type epoxy resin, orthocresol novolac type epoxy resin, trishydroxyphenylmethane type epoxy resin, and tetraphenylolethane type epoxy resin. Examples of the epoxy resin include hydantoin type epoxy resin, trisglycidyl isocyanurate type epoxy resin, and glycidylamine type epoxy resin. The transparent adhesive sheet 10 may contain one type of epoxy resin or two or more types of epoxy resins.
[0037] When the transparent adhesive sheet 10 has the first composition, the content of the thermosetting resin in the transparent adhesive sheet 10 is preferably 1 to 80 mass %, and more preferably 1 to 50 mass %, from the viewpoint of allowing the transparent adhesive sheet 10 to properly exhibit its function as a thermosetting adhesive.
[0038] When an epoxy resin is used as the thermosetting resin in the transparent adhesive sheet 10, a phenol resin and an imidazole-based curing agent are preferable as a curing agent for imparting thermosetting properties to the epoxy resin.
[0039] Examples of phenolic resins that can act as a curing agent for epoxy resins include novolac-type phenolic resins, resol-type phenolic resins, and polyoxystyrenes such as polyparaoxystyrene. Examples of novolac-type phenolic resins include phenol novolac resins, phenol aralkyl resins, cresol novolac resins, tert-butylphenol novolac resins, and nonylphenol novolac resins. The transparent adhesive sheet 10 may contain one type of phenolic resin, or two or more types of phenolic resins.
[0040] Examples of the imidazole-based curing agent include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-methyl-4-ethylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2 Examples of the imidazole curing agent include 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole. When the transparent adhesive sheet 10 contains an imidazole curing agent, the content of the imidazole curing agent in the transparent adhesive sheet is preferably 0.1 to 2 mass%, more preferably 0.2 to 1.5 mass%.
[0041] The thermoplastic resin in the transparent adhesive sheet 10, for example, serves as a binder, and examples of the thermoplastic resin in the transparent adhesive sheet 10 when the transparent adhesive sheet 10 has the first composition include acrylic resin, natural rubber, butyl rubber, isoprene rubber, chloroprene rubber, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, polybutadiene resin, polycarbonate resin, thermoplastic polyimide resin, polyamide resin such as 6-nylon and 6,6-nylon, phenoxy resin, saturated polyester resin such as polyethylene terephthalate and polybutylene terephthalate, polyamideimide resin, and fluororesin. The transparent adhesive sheet 10 may contain one type of thermoplastic resin or two or more types of thermoplastic resin. Acrylic resin is preferable as the thermoplastic resin in the transparent adhesive sheet 10 because it has few ionic impurities and high heat resistance.
[0042] When the transparent adhesive sheet 10 contains an acrylic resin as a thermoplastic resin, the acrylic polymer constituting the acrylic resin preferably contains a monomer unit derived from a (meth)acrylic acid ester in the largest amount by mass. "(Meth)acrylic" means "acrylic" and / or "methacrylic".
[0043] Examples of (meth)acrylic acid esters for forming the monomer units of the above acrylic polymer, that is, (meth)acrylic acid esters that are constituent monomers of the acrylic polymer, include (meth)acrylic acid alkyl esters, (meth)acrylic acid cycloalkyl esters, and (meth)acrylic acid aryl esters. Examples of (meth)acrylic acid alkyl esters include (meth)acrylic acid methyl ester, ethyl ester, propyl ester, isopropyl ester, butyl ester, isobutyl ester, s-butyl ester, t-butyl ester, pentyl ester, isopentyl ester, hexyl ester, heptyl ester, octyl ester, 2-ethylhexyl ester, isooctyl ester, nonyl ester, decyl ester, isodecyl ester, undecyl ester, dodecyl ester, tridecyl ester, tetradecyl ester, hexadecyl ester, octadecyl ester, and eicosyl ester. Examples of (meth)acrylic acid cycloalkyl esters include (meth)acrylic acid cyclopentyl ester and cyclohexyl ester. Examples of (meth)acrylic acid aryl esters include phenyl (meth)acrylate and benzyl (meth)acrylate. As a constituent monomer of an acrylic polymer, one type of (meth)acrylic acid ester may be used, or two or more types of (meth)acrylic acid esters may be used. In addition, an acrylic polymer for forming an acrylic resin can be obtained by polymerizing raw material monomers for forming the polymer. Examples of polymerization methods include solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization.
[0044] The acrylic polymer may contain one or more other monomers copolymerizable with the (meth)acrylic acid ester as a constituent monomer, for example, to improve its cohesive strength or heat resistance. Examples of such monomers include carboxy group-containing monomers, acid anhydride monomers, hydroxy group-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, acrylamide, and acrylonitrile. Examples of carboxy group-containing monomers include acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of acid anhydride monomers include maleic anhydride and itaconic anhydride. Examples of hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. Examples of sulfonic acid group-containing monomers include styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, and (meth)acryloyloxynaphthalenesulfonic acid. Examples of phosphoric acid group-containing monomers include 2-hydroxyethyl acryloyl phosphate. From the viewpoint of realizing high cohesive force in the transparent adhesive sheet 10, when the transparent adhesive sheet 10 contains an acrylic resin, the acrylic polymer for forming the acrylic resin is a nitrile group-containing acrylic polymer. The nitrile group-containing acrylic polymer is, for example, an acrylic polymer containing acrylonitrile as a constituent monomer, and examples of such acrylic polymers include copolymers of ethyl acrylate, butyl acrylate, and acrylonitrile.
[0045] When the transparent adhesive sheet 10 has the first composition, the content of the thermoplastic resin in the transparent adhesive sheet 10 is preferably 30 to 95 mass %, and more preferably 35 to 90 mass %, from the viewpoint of adequately exerting the binder function of the thermoplastic adhesive.
[0046] When the transparent adhesive sheet 10 has the second composition, the thermoplastic resin with a thermosetting functional group in the transparent adhesive sheet 10 can be, for example, an acrylic resin with a thermosetting functional group. The acrylic polymer for forming the acrylic skeleton of the acrylic resin with a thermosetting functional group preferably contains a monomer unit derived from a (meth)acrylic acid ester in the largest amount by mass ratio. As such a (meth)acrylic acid ester, for example, the above-mentioned (meth)acrylic acid ester can be used as the constituent monomer of the acrylic polymer described above when the transparent adhesive sheet 10 has the first composition. The acrylic polymer for forming the acrylic skeleton of the thermosetting functional group-containing acrylic resin may contain one or more other monomers copolymerizable with the (meth)acrylic acid ester as a constituent monomer, for example, to improve the cohesive force or heat resistance of the acrylic resin. Examples of such other constituent monomers include carboxyl group-containing monomers, acid anhydride monomers, hydroxyl group-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, acrylamide, and acrylonitrile. Specifically, the above-mentioned other copolymerizable constituent monomers can be used as the constituent monomers of the acrylic polymer described above when the transparent adhesive sheet 10 has the first composition. From the viewpoint of realizing high cohesive strength in the transparent adhesive sheet 10, the acrylic polymer for forming the acrylic skeleton of the acrylic resin with a thermosetting functional group in the transparent adhesive sheet 10 is a nitrile group-containing acrylic polymer. The nitrile group-containing acrylic polymer is, for example, an acrylic polymer containing acrylonitrile as a constituent monomer, and examples of such acrylic polymers include copolymers of ethyl acrylate, butyl acrylate, and acrylonitrile.
[0047] Examples of the thermosetting functional group for forming the thermoplastic resin having a thermosetting functional group include an epoxy group, a carboxy group, a hydroxy group, and an isocyanate group, and an epoxy group is preferred. The thermoplastic resin having a thermosetting functional group is preferably a thermoplastic resin having an epoxy group. When the transparent adhesive sheet 10 contains an epoxy group-containing thermoplastic resin, the transparent adhesive sheet 10 preferably contains an imidazole-based curing agent as a curing agent. Specific examples of the imidazole-based curing agent are as described above. When the transparent adhesive sheet 10 contains an imidazole-based curing agent, the content of the imidazole-based curing agent in the transparent adhesive sheet is preferably 0.1 to 2 mass%, more preferably 0.2 to 1.5 mass%.
[0048] When the transparent adhesive sheet 10 has the second composition, the content of the thermosetting functional group-containing acrylic resin, such as the nitrile group-containing acrylic resin, in the transparent adhesive sheet 10 is preferably 50% by mass or more, more preferably 60% by mass or more, more preferably 80% by mass or more, more preferably 95% by mass or more, and more preferably 97% by mass or more. Furthermore, when the transparent adhesive sheet 10 has the second composition, the transparent adhesive sheet 10 does not need to further contain a thermosetting resin, and preferably does not contain or substantially does not contain an epoxy resin and / or a phenol resin.
[0049] The average molecular weight of the thermoplastic resin such as acrylic resin contained in the transparent adhesive sheet 10 when the transparent adhesive sheet 10 has the first composition, and the average molecular weight of the thermoplastic resin with a thermosetting functional group contained in the transparent adhesive sheet 10 when the transparent adhesive sheet 10 has the second composition, are preferably 450,000 or less, more preferably 400,000 or less. Such a configuration is suitable for realizing the above-mentioned preferred configuration regarding the viscosity of the transparent adhesive sheet.
[0050] The transparent adhesive sheet 10 may contain a filler. Blending a filler into the transparent adhesive sheet 10 is preferable in terms of adjusting the physical properties of the transparent adhesive sheet 10, such as the elastic modulus, viscosity, breaking strength, and breaking elongation. Examples of the filler include inorganic fillers and organic fillers. Examples of the constituent materials of the inorganic filler include aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whiskers, boron nitride, crystalline silica, and amorphous silica. Examples of the constituent materials of the inorganic filler include simple metals such as aluminum, gold, silver, copper, and nickel, alloys, amorphous carbon, and graphite. Examples of the constituent materials of the organic filler include polymethylmethacrylate (PMMA), polyimide, polyamideimide, polyetheretherketone, polyetherimide, and polyesterimide. The transparent adhesive sheet 10 may contain one type of filler, or may contain two or more types of fillers. The filler may have various shapes, such as spherical, acicular, or flake-like.
[0051] When the transparent adhesive sheet 10 contains a filler, the average particle size of the filler is preferably 5 to 100 nm, more preferably 5 to 60 nm. The average particle size of the filler can be determined, for example, by using a photometric particle size distribution meter (product name "LA-910", manufactured by Horiba, Ltd.). When the transparent adhesive sheet 10 contains a filler, the content of the filler is preferably 5 to 45 mass %, more preferably 6 to 40 mass %, more preferably 7 to 35 mass %. These configurations are suitable for ensuring the heat resistance of the transparent adhesive sheet 10, and therefore suitable for ensuring the bonding reliability between objects bonded by the transparent adhesive sheet 10. These configurations also contribute to ensuring the transparency of the transparent adhesive sheet 10.
[0052] The transparent adhesive sheet 10 may contain an antioxidant. Examples of the antioxidant include phosphorus-based antioxidants, phenol-based antioxidants, and thioether-based antioxidants. The transparent adhesive sheet 10 preferably contains a phosphorus-based antioxidant. Examples of the phosphorus-based antioxidant include 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, and 2,2'-methylenebis(4,6-di-tert-butylphenyl)2-ethylhexylphosphite. When the transparent adhesive sheet 10 contains an antioxidant such as a phosphorus-based antioxidant, the content of the antioxidant in the transparent adhesive sheet 10 is preferably 0.1 to 2 mass %, more preferably 0.3 to 1.5 mass %.
[0053] If necessary, the transparent adhesive sheet 10 may contain one or more other components, such as a flame retardant, a silane coupling agent, and an ion trapping agent.
[0054] The thickness of the transparent adhesive sheet 10 is preferably 5 μm or more, more preferably 10 μm or more, and more preferably 20 μm or more. Also, the thickness of the transparent adhesive sheet 10 is preferably 150 μm or less, more preferably 140 μm or less, more preferably 130 μm or less, and more preferably 120 μm or less.
[0055] The transparent adhesive sheet 10, when thermally cured by heating at 150° C. for 1 hour, has a transmittance in the wavelength range of 450 to 1200 nm of 85% or more, preferably 87% or more, and more preferably 90% or more.
[0056] In the transparent adhesive sheet 10, in a heat-cured state by heating at 150° C. for 1 hour, the ratio (first ratio) of the transmittance at a wavelength of 450 nm after a moisture absorption test under conditions (first conditions) of 30° C., relative humidity of 70%, and 200 hours to the transmittance at a wavelength of 450 nm before the moisture absorption test is preferably 0.9 or more, more preferably 0.92 or more, and more preferably 0.94 or more. The first ratio is, for example, 1 or less.
[0057] In the transparent adhesive sheet 10, in a heat-cured state by heating at 150° C. for 1 hour, the ratio (second ratio) of the transmittance at a wavelength of 450 nm after a heating test under conditions (second conditions) of 260° C. for 5 minutes to the transmittance at a wavelength of 450 nm before the heating test is preferably 0.9 or more, more preferably 0.92 or more, and more preferably 0.94 or more. The second ratio is, for example, 1 or less.
[0058] The viscosity of the transparent adhesive sheet 10 or the adhesive composition constituting it at 120° C. is preferably 1 to 30 kPa·s, more preferably 3 to 30 kPa·s, more preferably 4 to 27 kPa·s, and more preferably 5 to 25 kPa·s.
[0059] The transparent adhesive sheet 10 has a storage modulus at 250° C. in a heat-cured state after heating at 150° C. for 1 hour of preferably 0.5 to 50 MPa, more preferably 0.6 to 45 MPa, and more preferably 0.7 to 40 MPa.
[0060] When the transparent adhesive sheet 10 is in a heat-cured state by heating at 150°C for 1 hour, the weight loss rate at 300°C when measured by thermogravimetry under conditions of a nitrogen atmosphere, a heating rate of 10°C / min, and a heating range of 23 to 300°C is preferably 1.5% or less, and more preferably 1.2% or less.
[0061] The transparent adhesive sheet 10 exhibits a peel adhesion strength of 1 N / 10 mm or more, preferably 1.5 N / 10 mm or more, against a flat glass surface in a peel test under conditions of 23° C., a peel angle of 180°, and a peel speed of 30 mm / min.
[0062] The transparent adhesive sheet 10 has a glass shear adhesive strength in a state where it is heated at 150°C for 1 hour and then adhered to a flat glass surface (glass-adhered state) such that the ratio (third ratio) of the glass shear adhesive strength after a moisture absorption test under conditions (third conditions) of 40°C, relative humidity of 95% and 120 hours in the glass-adhered state to the glass shear adhesive strength in the glass-adhered state is preferably 0.6 or more, more preferably 0.7 or more, and more preferably 0.75 or more. The third ratio is, for example, 1.5 or less, and may be 1 or less.
[0063] The transparent adhesive sheet 10 preferably has a refractive index at a wavelength of 633 nm in a heat-cured state after heating at 150° C. for 1 hour of 1.4 to 1.5, and more preferably 1.42 to 1.48.
[0064] The release liners R1 and R2 in the transparent adhesive sheet X1 with a release material are elements for covering and protecting the surface of the transparent adhesive sheet 10, and are peeled off from the sheet when using the transparent adhesive sheet 10. As the release liners R1 and R2, a resin film or paper material having a surface to which the transparent adhesive sheet 10 will be adhered that has been subjected to, for example, corona treatment and subsequent release treatment can be used.
[0065] Examples of resin materials for forming the resin film for the release liner include polyolefins and polyesters. Examples of polyolefins include low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, very low-density polyethylene, random copolymer polypropylene, block copolymer polypropylene, homopolypropylene, polybutene, polymethylpentene, ethylene-vinyl acetate copolymer (EVA), ionomer resin, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylic acid ester copolymer, ethylene-butene copolymer, and ethylene-hexene copolymer. Examples of polyesters include polyethylene terephthalate (PET), polyethylene naphthalate, and polybutylene terephthalate (PBT). The resin film for the release liner may be a non-stretched film, a uniaxially stretched film, or a biaxially stretched film. Each of the release liners R1 and R2 may be made of one type of material, or two or more types of materials. The release liners R1 and R2 may have a single-layer structure or a multilayer structure. Examples of the release agent used in the above release treatment include silicone-based release agents, long-chain alkyl-based release agents, fluorine-based release agents, and molybdenum sulfide release agents.
[0066] In the transparent adhesive sheet X1 with a release material, the thickness T1 of the release liner R1 (first release material) is preferably 38 μm or more, and the thickness T2 of the release liner R2 (second release material) is preferably 25 μm or more. The ratio (T1 / T2) of the thickness T1 of the release liner R1 to the thickness T2 of the release liner R2 is preferably 0.2 to 1.8, more preferably 0.22 to 1.6, and more preferably 0.3 to 1.55. Such a configuration is preferable from the viewpoint of workability when handling the transparent adhesive sheet X1 with a release material. Specifically, this configuration is suitable for preventing or suppressing the occurrence of wrinkles or folds in the transparent adhesive sheet 10 when the release liner R1 is peeled off from the transparent adhesive sheet 10 (which has the release liner R2 on the side opposite to the release liner R1) in the transparent adhesive sheet X1 with a release material.
[0067] In transparent adhesive sheet X1 with a release liner, release liner R1 (first release liner) exhibits a first peel adhesion strength of preferably 0.01 N / 100 mm or more, more preferably 0.015 N / 100 mm or more, to transparent adhesive sheet 10 in a peel test at 100°C, a peel angle of 180°, and a peel speed of 300 mm / min, and release liner R2 (second release liner) exhibits a second peel adhesion strength of preferably 0.04 N / 100 mm or more, to transparent adhesive sheet 10 in a peel test at 100°C, a peel angle of 180°, and a peel speed of 300 mm / min. The ratio of the first peel adhesion strength to the second peel adhesion strength is preferably 0.01 to 0.75, more preferably 0.02 to 0.7. These configurations are preferable from the viewpoint of a balance between sufficient adhesion of the release liners R1, R2 (which are often peeled off separately from the transparent adhesive sheet 10 at different stages) to the transparent adhesive sheet 10 during handling of the release-material-attached transparent adhesive sheet X1 and appropriate releasability of the release liners R1, R2 from the transparent adhesive sheet 10. If the adhesion is insufficient, the release liners R1, R2 may be accidentally peeled off from the transparent adhesive sheet 10 during handling. Furthermore, if appropriate releasability is not ensured between the transparent adhesive sheet 10 and the release liners R1, R2, peeling failure or so-called tearful separation may occur when peeling each release liner from the transparent adhesive sheet 10.
[0068] The transparent adhesive sheet X1 with a release material having the above-mentioned configuration can be produced, for example, as follows. First, an adhesive composition for forming the transparent adhesive sheet 10 is prepared, and then the composition is applied onto a long release liner R1 to form a long adhesive composition layer. Examples of the adhesive composition application method include roll coating, screen coating, and gravure coating. Next, the adhesive composition layer is dried on the release liner R1 to form an adhesive layer. Next, a long, predetermined separator (first separator) is laminated on and along the adhesive layer. Next, each transparent adhesive sheet 10 of a predetermined shape is formed on the release liner R1 by punching a processing blade from the side of the first separator to the release liner R1. Each transparent adhesive sheet 10 has a shape and size according to the planned adhesive supply location on the joining object, for example, and is arranged in a row in the extension direction of the long release liner R1. Next, the first separator and the adhesive layer material between the transparent adhesive sheets 10 are removed from the release liner R1 while leaving the formed transparent adhesive sheet 10 on the release liner R1. Next, another long separator (second separator) is laminated on the multiple transparent adhesive sheets 10 so as to cover the multiple transparent adhesive sheets 10 arranged at a distance on the long release liner R1. Next, a release liner R2 having a predetermined shape is formed by punching the second separator, and the second separator material between the release liners R2 is removed. For example, the transparent adhesive sheet X1 with a release material can be produced as described above. In the transparent adhesive sheet X1 with a release material, one long transparent adhesive sheet 10 to be cut into small pieces as necessary may be disposed between a pair of long release liners R1 and R2. The transparent adhesive sheet X1 with a release material may also be wound around a core to form a roll.
[0069] 2 shows a state in which the detection surface 1a of the optical sensor 1 and the transparent cover member 2 are joined by a thermally cured transparent adhesive sheet 10 or an adhesive layer 11 derived therefrom. The optical sensor is, for example, an optical fingerprint authentication sensor. The transparent cover member 2 is, for example, a glass or transparent resin member having a transmittance of 80% or more at a wavelength of 500 nm. With the transparent adhesive sheet 10 of a predetermined size in an uncured state interposed between the optical sensor 1 and the transparent cover member 2, which are objects to be joined, the transparent adhesive sheet 10 is thermally cured to join the detection surface 1a of the optical sensor 1 and the transparent cover member 2.
[0070] According to the transparent adhesive sheet 10 as described above, it is possible to supply an adhesive material between objects to be joined in the form of a sheet that can be produced with high uniformity in thickness and is difficult to flow (an adhesive material that is difficult to flow is less likely to overflow from between the objects to be joined during the joining process). Therefore, according to the transparent adhesive sheet 10, it is possible to join the objects to be joined, that is, the optical sensor 1 and the transparent cover member 2, with an adhesive layer 11 having a high uniformity in thickness, compared to the case of using a liquid adhesive. Being able to join the optical sensor 1 and the transparent cover member 2 with an adhesive layer 11 having a high uniformity in thickness is suitable for joining the optical sensor 1 to the transparent cover member 2 with good posture accuracy, and is also suitable for manufacturing a device in which the optical sensor 1 is incorporated with good yield.
[0071] In addition, as described above, the transparent adhesive sheet 10 has a transmittance of 85% or more, preferably 87% or more, and more preferably 90% or more in the wavelength range of 450 to 1200 nm when thermally cured by heating at 150° C. for 1 hour. The transparent adhesive sheet 10 has such a light transmittance over the wavelength range from visible light to near infrared light after thermal curing, and is suitable for use as a bonding material between the detection surface 1a of the optical sensor 1 and the transparent cover member 2 to ensure effective detection sensitivity of the optical sensor 1 in a device.
[0072] As described above, the transparent adhesive sheet 10 is suitable as a bonding material between the detection surface 1a of the optical sensor 1 and the transparent cover member 2, for manufacturing devices equipped with an optical sensor with good yield, and for ensuring the detection sensitivity of the sensor.
[0073] As described above, the transparent adhesive sheet 10, in a heat-cured state by heating at 150° C. for 1 hour, has a ratio (first ratio) of the transmittance at a wavelength of 450 nm after the moisture absorption test under conditions (first conditions) of 30° C., relative humidity of 70%, and 200 hours to the transmittance at a wavelength of 450 nm before the moisture absorption test, of preferably 0.9 or more, more preferably 0.92 or more, and more preferably 0.94 or more. The transparent adhesive sheet 10 having such a small decrease in transmittance after the moisture absorption test under the first conditions is suitable as a bonding material between the detection surface 1a of the optical sensor 1 and the transparent cover member 2 in order to ensure the effective detection sensitivity of the optical sensor 1 in the device.
[0074] As described above, the transparent adhesive sheet 10, in a heat-cured state by heating at 150° C. for 1 hour, has a ratio (second ratio) of the transmittance at a wavelength of 450 nm after a heating test under conditions (second conditions) of 260° C. for 5 minutes to the transmittance at a wavelength of 450 nm before the heating test, of preferably 0.9 or more, more preferably 0.92 or more, and more preferably 0.94 or more. A configuration in which the decrease in transmittance in the transparent adhesive sheet 10 due to the heating test under the second conditions is this small is suitable for ensuring the above-mentioned sensor detection sensitivity.
[0075] As described above, the viscosity of the transparent adhesive sheet 10 or the adhesive composition constituting it at 120°C is preferably 1 to 30 kPa·s, more preferably 3 to 30 kPa·s, more preferably 4 to 27 kPa·s, and more preferably 5 to 25 kPa·s. Such a configuration is suitable for ensuring good wettability of the transparent adhesive sheet 10 to objects to be joined, such as the optical sensor 1 and the transparent cover member 2.
[0076] As described above, the transparent adhesive sheet 10 has a storage modulus at 250° C. in a heat-cured state by heating at 150° C. for 1 hour of preferably 0.5 to 50 MPa, more preferably 0.6 to 45 MPa, and more preferably 0.7 to 40 MPa. Such a configuration is suitable for ensuring the bonding strength of the transparent adhesive sheet 10 after curing between objects to be bonded, such as between the optical sensor 1 and the transparent cover member 2, and is therefore suitable for ensuring the bonding reliability between objects to be bonded by the transparent adhesive sheet 10.
[0077] As described above, the transparent adhesive sheet 10, in a heat-cured state by heating at 150° C. for 1 hour, preferably exhibits a weight loss rate of 1.5% or less, more preferably 1.2% or less at 300° C., as measured by thermogravimetry under conditions of a nitrogen atmosphere, a heating rate of 10° C. / min, and a heating range of 23 to 300° C. Such a configuration is suitable for ensuring heat resistance in the transparent adhesive sheet 10, and is therefore suitable for ensuring the bonding reliability of objects such as the optical sensor 1 and the transparent cover member 2 bonded by the transparent adhesive sheet 10.
[0078] As described above, the transparent adhesive sheet 10 exhibits a peel adhesion strength of 1 N / 10 mm or more, preferably 1.5 N / 10 mm or more, against a flat glass surface in a peel test under conditions of 23° C., a peel angle of 180°, and a peel speed of 30 mm / min. Such a configuration is suitable for ensuring the adhesive strength of the transparent adhesive sheet 10 to objects to be joined, such as the optical sensor 1 and the transparent cover member 2.
[0079] As described above, the transparent adhesive sheet 10 has a ratio (third ratio) of the glass shear adhesive strength after a moisture absorption test under conditions (third conditions) of 40°C, relative humidity of 95% and 120 hours in the glass-bonded state to the glass shear adhesive strength in a state (glass-bonded state) after heating at 150°C for 1 hour, which is preferably 0.6 or more, more preferably 0.7 or more, and more preferably 0.75 or more. The configuration in which the decrease in the glass shear adhesive strength of the transparent adhesive sheet 10 due to the moisture absorption test under the third conditions is so small is suitable for ensuring the bonding reliability of the objects bonded by the transparent adhesive sheet 10, such as the optical sensor 1 and the transparent cover member 2.
[0080] As described above, the transparent adhesive sheet 10 preferably has a refractive index of 1.4 to 1.5, and more preferably 1.42 to 1.48 at a wavelength of 633 nm in a heat-cured state after heating for 1 hour at 150° C. Such a configuration is suitable for ensuring the above-mentioned sensor detection sensitivity.
[0081] As described above, the transparent adhesive sheet 10 preferably contains an acrylic resin, and this acrylic resin preferably has a nitrile group and preferably has an epoxy group. The ratio of the acrylic resin in the organic components contained in the transparent adhesive sheet 10 is preferably 95% by mass or more, more preferably 97% by mass or more. In addition, the transparent adhesive sheet 10 preferably does not contain or substantially does not contain an epoxy resin and / or a phenol resin. These configurations are suitable for achieving the high degree of transparency in the transparent adhesive sheet 10 as described above.
[0082] When the transparent adhesive sheet 10 contains an acrylic resin such as a nitrile group-containing acrylic resin, the average molecular weight of the acrylic resin is preferably 450,000 or less, more preferably 400,000 or less, as described above. Such a configuration is suitable for realizing the above-mentioned preferred configuration regarding the viscosity of the transparent adhesive sheet 10.
[0083] As described above, the transparent adhesive sheet 10 preferably contains a filler having an average particle size of 5 to 100 nm. As described above, the content of the filler in the transparent adhesive sheet 10 is preferably 5 to 40 mass %, more preferably 7 to 35 mass %. These configurations are suitable for ensuring heat resistance in the transparent adhesive sheet 10, and are therefore suitable for ensuring bonding reliability for objects such as the optical sensor 1 and the transparent cover member 2 bonded by the transparent adhesive sheet 10. In addition, these configurations also contribute to ensuring the transparency of the transparent adhesive sheet 10 as described above.
[0084] As described above, the transparent adhesive sheet 10 preferably contains a phosphorus-based antioxidant. As described above, the content of the phosphorus-based antioxidant in the transparent adhesive sheet 10 is preferably 0.1 to 2 mass %, more preferably 0.3 to 1.5 mass %. These configurations are suitable for preventing and suppressing oxidation of the components contained in the transparent adhesive sheet 10, and therefore are suitable for preventing and suppressing a decrease in transparency due to the oxidation.
[0085] As described above, the transparent adhesive sheet 10 preferably contains an imidazole-based curing agent. As described above, the content of the imidazole-based curing agent in the transparent adhesive sheet 10 is preferably 0.1 to 2 mass %, more preferably 0.2 to 1.5 mass %. Such a configuration is suitable for achieving both the curability and storage stability of the transparent adhesive sheet 10.
[0086] 3 is a cross-sectional schematic diagram of a release-material-attached transparent adhesive sheet X2 according to one embodiment of the present invention. The release-material-attached transparent adhesive sheet X2 has a laminated structure including a transparent adhesive sheet 10 according to one embodiment of the present invention, a release liner R1 as one release material (second release material), and a dicing tape 20 as the other release material (second release material). With regard to the laminated structure, the release-material-attached transparent adhesive sheet X2 differs from the release-material-attached transparent adhesive sheet X1 described above in that it includes a dicing tape 20 as the second release material instead of the release liner R2.
[0087] The dicing tape 20 has a laminated structure including a substrate 21 and an adhesive layer 22. The adhesive layer 22 has an adhesive surface 22a on the transparent adhesive sheet 10 side. The transparent adhesive sheet 10 is releasably attached to the adhesive layer 22 or its adhesive surface 22a of the dicing tape 20. Such a transparent adhesive sheet X2 with a release material can be used, for example, to obtain an optical sensor with a transparent adhesive layer in the manufacturing process of a device equipped with an optical sensor. In addition, the dicing tape 20 and the transparent adhesive sheet 10 have a disk shape of a size to which a workpiece having a plurality of optical sensors can be attached, and are arranged concentrically in this embodiment. In other respects, such as the constituent materials of the transparent adhesive sheet 10, the transparent adhesive sheet X2 with a release material is the same as the transparent adhesive sheet X1 with a release material.
[0088] The substrate 21 of the dicing tape 20 in the transparent adhesive sheet X2 with a release material is an element that functions as a support in the dicing tape 20 or the transparent adhesive sheet X2 with a release material. The substrate 21 is, for example, a plastic substrate, and a plastic film can be suitably used as the plastic substrate. Examples of the constituent material of the plastic substrate include polyolefin, polyester, polyurethane, polycarbonate, polyether ether ketone, polyimide, polyetherimide, polyamide, wholly aromatic polyamide, polyvinyl chloride, polyvinylidene chloride, polyphenyl sulfide, aramid, fluororesin, cellulose-based resin, and silicone resin. Examples of polyolefin include low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, very low-density polyethylene, random copolymer polypropylene, block copolymer polypropylene, homopolypropylene, polybutene, polymethylpentene, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylic acid ester copolymer, ethylene-butene copolymer, and ethylene-hexene copolymer. Examples of polyester include polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate. The substrate 21 may be made of one type of material, or may be made of two or more types of materials. The substrate 21 may have a single-layer structure or a multi-layer structure. When the adhesive layer 22 on the substrate 21 has ultraviolet curing properties, the substrate 21 is preferably ultraviolet transparent.
[0089] The surface of the substrate 21 on the side of the adhesive layer 22 may be subjected to a physical treatment, a chemical treatment, or a primer treatment in order to enhance adhesion to the adhesive layer 22. Examples of the physical treatment include a corona treatment, a plasma treatment, a sand mat processing treatment, an ozone exposure treatment, a flame exposure treatment, a high-voltage shock exposure treatment, and an ionizing radiation treatment. Examples of the chemical treatment include a chromate treatment.
[0090] The thickness of the substrate 21 is preferably 40 μm or more, more preferably 50 μm or more, from the viewpoint of ensuring the strength required for the substrate 21 to function as a support in the dicing tape 20 or the transparent adhesive sheet X2 with a release material. In addition, from the viewpoint of realizing appropriate flexibility in the dicing tape 20 or the transparent adhesive sheet X2 with a release material, the thickness of the substrate 21 is preferably 200 μm or less, more preferably 180 μm or less.
[0091] The adhesive layer 22 of the dicing tape 20 contains an adhesive. This adhesive may be an adhesive (adhesive strength reducing adhesive) whose adhesive strength can be intentionally reduced by an external action during the use of the transparent adhesive sheet X2 with a release material, or an adhesive (non-adhesive strength reducing adhesive) whose adhesive strength is hardly or not reduced by an external action during the use of the transparent adhesive sheet X2 with a release material. Whether an adhesive strength reducing adhesive or an adhesive strength non-reducing adhesive is used as the adhesive in the adhesive layer 22 can be appropriately selected according to the use mode of the transparent adhesive sheet X2 with a release material. When an adhesive strength reducing adhesive is used as the adhesive in the adhesive layer 22, it is possible to selectively use a state in which the adhesive layer 22 exhibits a relatively high adhesive strength and a state in which the adhesive layer 22 exhibits a relatively low adhesive strength during the use of the transparent adhesive sheet X2 with a release material.
[0092] Examples of the above-mentioned adhesive-reduced type adhesive include an adhesive (radiation-curable adhesive) that can be cured by radiation exposure during the use of the transparent adhesive sheet X2 with a release material, and a heat-foaming type adhesive. In the adhesive layer 22 of this embodiment, one type of adhesive-reduced type adhesive may be used, or two or more types of adhesive-reduced type adhesives may be used. In addition, the entire adhesive layer 22 may be formed from an adhesive-reduced type adhesive, or a part of the adhesive layer 22 may be formed from an adhesive-reduced type adhesive. For example, when the adhesive layer 22 has a single-layer structure, the entire adhesive layer 22 may be formed from an adhesive-reduced type adhesive, or a predetermined part of the adhesive layer 22 may be formed from an adhesive-reduced type adhesive, and the other part may be formed from an adhesive that does not reduce adhesion. In addition, when the adhesive layer 22 has a multilayer structure, all layers constituting the multilayer structure may be formed from an adhesive-reduced type adhesive, or a part of the layers in the multilayer structure may be formed from an adhesive-reduced type adhesive.
[0093] Examples of radiation-curable adhesives for the adhesive layer 22 include adhesives that are cured by irradiation with electron beams, ultraviolet rays, alpha rays, beta rays, gamma rays, or X-rays, and adhesives that are cured by ultraviolet irradiation (ultraviolet-curable adhesives) are particularly suitable for use.
[0094] An example of the radiation-curable adhesive for the adhesive layer 22 is an additive-type radiation-curable adhesive that contains a base polymer such as an acrylic polymer that is an acrylic adhesive, and a radiation-polymerizable monomer component or oligomer component that has a functional group such as a radiation-polymerizable carbon-carbon double bond.
[0095] The acrylic polymer as the base polymer of the radiation curable adhesive preferably contains the most monomer unit derived from (meth)acrylic acid ester in terms of mass ratio. Examples of the (meth)acrylic acid ester for forming the monomer unit of the acrylic polymer, that is, the (meth)acrylic acid ester as the constituent monomer of the acrylic polymer, include (meth)acrylic acid alkyl ester, (meth)acrylic acid cycloalkyl ester, and (meth)acrylic acid aryl ester. More specifically, the (meth)acrylic acid ester includes the above-mentioned (meth)acrylic acid ester as the constituent monomer of the acrylic polymer for forming the acrylic resin for the transparent adhesive sheet 10. As the constituent monomer of the acrylic polymer, one type of (meth)acrylic acid ester may be used, or two or more types of (meth)acrylic acid esters may be used. As the constituent monomer of the acrylic polymer, preferably, 2-ethylhexyl acrylate is used. That is, the acrylic polymer as the acrylic adhesive in the adhesive layer 22 preferably has a 2-ethylhexyl group. Such a configuration is suitable for realizing high adhesion between the adhesive layer 22 of the dicing tape 20 and the transparent adhesive sheet 10. In order to properly exhibit basic properties such as adhesion due to the (meth)acrylic acid ester in the adhesive layer 22, the ratio of the (meth)acrylic acid ester to all the constituent monomers of the acrylic polymer is preferably 40 mass % or more, more preferably 60 mass % or more.
[0096] The acrylic polymer may contain one or more other monomers copolymerizable with (meth)acrylic acid esters as constituent monomers, for example, to improve its cohesive strength or heat resistance. Examples of such other monomers include carboxyl group-containing monomers, acid anhydride monomers, hydroxyl group-containing monomers, epoxy group-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, acrylamide, and acrylonitrile. More specifically, the other monomers include the copolymerizable other constituent monomers described above as constituent monomers of the acrylic polymer for forming the acrylic resin for the transparent adhesive sheet 10.
[0097] The acrylic polymer serving as the acrylic adhesive for forming the adhesive layer 22 may contain a monomer unit derived from a polyfunctional monomer copolymerizable with a monomer component such as a (meth)acrylic acid ester in order to form a crosslinked structure in the polymer skeleton. Examples of such polyfunctional monomers include hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, polyglycidyl (meth)acrylate, polyester (meth)acrylate, and urethane (meth)acrylate. "(Meth)acrylate" means "acrylate" and / or "methacrylate". As the constituent monomer of the acrylic polymer, one type of polyfunctional monomer may be used, or two or more types of polyfunctional monomers may be used. In order to appropriately express basic properties such as adhesion due to (meth)acrylic acid ester in the adhesive layer 22, the ratio of the polyfunctional monomer to the entire constituent monomer of the acrylic polymer is preferably 40 mass % or less, and preferably 30 mass % or less.
[0098] The acrylic polymer can be obtained by polymerizing the raw material monomer for forming it. Examples of the polymerization method include solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization. From the viewpoint of high cleanliness in, for example, a semiconductor device manufacturing process in which the dicing tape 20 or the transparent adhesive sheet X2 with a release material is used, it is preferable that the amount of low molecular weight components in the adhesive layer 22 in the dicing tape 20 or the transparent adhesive sheet X2 with a release material is small, and the number average molecular weight of the acrylic polymer is preferably 100,000 or more, more preferably 200,000 to 3,000,000.
[0099] The adhesive layer 22 or an adhesive for forming the adhesive layer may contain, for example, an external crosslinking agent to increase the number average molecular weight of the base polymer such as an acrylic polymer. Examples of the external crosslinking agent for reacting with the base polymer such as an acrylic polymer to form a crosslinked structure include polyisocyanate compounds, epoxy compounds, polyol compounds, aziridine compounds, and melamine crosslinking agents. The content of the external crosslinking agent in the adhesive layer 22 or an adhesive for forming the adhesive layer is preferably 5 parts by mass or less, more preferably 0.1 to 5 parts by mass, based on 100 parts by mass of the base polymer.
[0100] Examples of the radiation-polymerizable monomer component for forming the radiation-curable adhesive include urethane (meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and 1,4-butanediol di(meth)acrylate. Examples of the radiation-polymerizable oligomer component for forming the radiation-curable adhesive include various oligomers such as urethane-based, polyether-based, polyester-based, polycarbonate-based, and polybutadiene-based oligomers, and those having a molecular weight of about 100 to 30,000 are suitable. The total content of radiation-polymerizable monomer components and oligomer components in the radiation-curable adhesive is determined within a range that allows an appropriate reduction in the adhesive strength of the formed adhesive layer 22, and is preferably 5 to 500 parts by mass, and more preferably 40 to 150 parts by mass, per 100 parts by mass of a base polymer such as an acrylic polymer. As an additive-type radiation-curable adhesive, for example, one disclosed in JP-A-60-196956 may be used.
[0101] Examples of the radiation-curable adhesive for the adhesive layer 22 include an intrinsic type radiation-curable adhesive containing a base polymer having a functional group such as a radiation-polymerizable carbon-carbon double bond on a polymer side chain, in a polymer main chain, or at the end of the polymer main chain. Such an intrinsic type radiation-curable adhesive is suitable for suppressing unintended changes over time in adhesive properties due to migration of low molecular weight components in the adhesive layer 22 to be formed.
[0102] The base polymer contained in the intrinsic radiation curable adhesive preferably has an acrylic polymer as a basic skeleton. As the acrylic polymer having such a basic skeleton, the above-mentioned acrylic polymer can be used as the base polymer contained in the additive radiation curable adhesive. As a method for introducing a radiation polymerizable carbon-carbon double bond into an acrylic polymer, for example, a method is exemplified in which a raw material monomer including a monomer having a specific functional group (first functional group) is copolymerized to obtain an acrylic polymer, and then a compound having a specific functional group (second functional group) capable of reacting with and bonding to the first functional group and a radiation polymerizable carbon-carbon double bond is subjected to a condensation reaction or addition reaction with the acrylic polymer while maintaining the radiation polymerizability of the carbon-carbon double bond.
[0103] Combinations of the first functional group and the second functional group include, for example, a carboxy group and an epoxy group, an epoxy group and a carboxy group, a carboxy group and an aziridyl group, an aziridyl group and a carboxy group, a hydroxy group and an isocyanate group, and an isocyanate group and a hydroxy group. Among these combinations, from the viewpoint of ease of reaction tracking, a combination of a hydroxy group and an isocyanate group, or a combination of an isocyanate group and a hydroxy group is preferred. In addition, since it is technically difficult to prepare a polymer having a highly reactive isocyanate group, from the viewpoint of ease of preparation or availability of an acrylic polymer, it is more preferred that the first functional group on the acrylic polymer side is a hydroxy group and the second functional group is an isocyanate group. Examples of isocyanate compounds having both a radiation-polymerizable carbon-carbon double bond and an isocyanate group as a second functional group, i.e., radiation-polymerizable unsaturated functional group-containing isocyanate compounds, include methacryloyl isocyanate, 2-methacryloyloxyethyl isocyanate (MOI), and m-isopropenyl-α,α-dimethylbenzyl isocyanate.
[0104] The radiation-curable adhesive for the adhesive layer 22 preferably contains a photopolymerization initiator. Examples of the photopolymerization initiator include α-ketol compounds, acetophenone compounds, benzoin ether compounds, ketal compounds, aromatic sulfonyl chloride compounds, photoactive oxime compounds, benzophenone compounds, thioxanthone compounds, camphorquinone, halogenated ketones, acylphosphinoxides, and acylphosphonates. The content of the photopolymerization initiator in the radiation-curable adhesive in the adhesive layer 22 is, for example, 0.05 to 20 parts by mass relative to 100 parts by mass of the base polymer such as an acrylic polymer.
[0105] An example of the non-reducing adhesive in the adhesive layer 22 is a pressure-sensitive adhesive. For example, an acrylic adhesive having an acrylic polymer as a base polymer or a rubber-based adhesive can be used as the pressure-sensitive adhesive. When the adhesive layer 22 contains an acrylic adhesive as the pressure-sensitive adhesive, the acrylic polymer as the base polymer of the acrylic adhesive preferably contains a monomer unit derived from a (meth)acrylic acid ester as the monomer unit having the largest mass ratio. For example, such an acrylic polymer can be the acrylic polymer described above with respect to the radiation-curable adhesive.
[0106] In the adhesive layer 22 of this embodiment, one type of adhesive force non-reduced type adhesive may be used, or two or more types of adhesive force non-reduced type adhesives may be used. The entire adhesive layer 22 may be formed from an adhesive force non-reduced type adhesive, or a part of the adhesive layer 22 may be formed from an adhesive force non-reduced type adhesive. For example, when the adhesive layer 22 has a single-layer structure, the entire adhesive layer 22 may be formed from an adhesive force non-reduced type adhesive, or a predetermined part of the adhesive layer 22 may be formed from an adhesive force non-reduced type adhesive, and the other part may be formed from an adhesive force reduced type adhesive. When the adhesive layer 22 has a laminated structure, all layers constituting the laminated structure may be formed from an adhesive force non-reduced type adhesive, or a part of the layers in the laminated structure may be formed from an adhesive force non-reduced type adhesive.
[0107] The adhesive layer 22 or the adhesive for forming the adhesive layer may contain, in addition to the above-mentioned components, a crosslinking accelerator, a tackifier, an antiaging agent, a colorant, etc. Examples of the colorant include pigments and dyes. The colorant may also be a compound that becomes colored when exposed to radiation. Examples of such compounds include leuco dyes.
[0108] The thickness of the adhesive layer 22 is preferably 5 to 40 μm, and more preferably 10 to 30 μm. Such a configuration is suitable for achieving high adhesion between the adhesive layer 22 of the dicing tape 20 and the transparent adhesive sheet 10.
[0109] The transparent adhesive sheet X2 with release material having the above-mentioned configuration can be produced, for example, by laminating a transparent adhesive sheet 10 to the adhesive layer 22 side of a dicing tape 20, and then providing a release liner R1 on the dicing tape 20 so as to cover the transparent adhesive sheet 10 and the surrounding surface of the adhesive layer 22.
[0110] In the transparent adhesive sheet X2 with a release material, the thickness T1 of the release liner R1 (first release material) is preferably 38 μm or more, and the thickness T2 of the dicing tape 20 (second release material) is preferably 25 μm or more. The ratio (T1 / T2) of the thickness T1 of the release liner R1 to the thickness T2 of the dicing tape 20 is preferably 0.2 to 1.8, more preferably 0.22 to 1.6, and even more preferably 0.3 to 1.55. Such a configuration is preferable from the viewpoint of workability when handling the transparent adhesive sheet X2 with a release material. Specifically, this configuration is suitable for preventing and suppressing the occurrence of wrinkles and folds in the transparent adhesive sheet 10 when the release liner R1 is peeled off from the transparent adhesive sheet 10 (with the dicing tape 20 on the side opposite to the release liner R1) in the transparent adhesive sheet X2 with a release material.
[0111] In the transparent adhesive sheet X2 with a release liner, the release liner R1 (first release material) exhibits a first peel adhesion strength of preferably 0.01 N / 100 mm or more, more preferably 0.015 N / 100 mm or more, to the transparent adhesive sheet 10 in a peel test under conditions of 100° C., a peel angle of 180°, and a peel speed of 300 mm / min, and the dicing tape 20 (second release material) exhibits a second peel adhesion strength of preferably 0.04 N / 100 mm or more, to the transparent adhesive sheet 10 in a peel test under conditions of 100° C., a peel angle of 180°, and a peel speed of 300 mm / min. The ratio of the first peel adhesion strength to the second peel adhesion strength is preferably 0.01 to 0.75, more preferably 0.02 to 0.7. These configurations are preferable from the standpoint of achieving a balance between sufficient adhesion of the release liner R1 and dicing tape 20 (which are often peeled off separately from the transparent adhesive sheet 10 at different stages) to the transparent adhesive sheet 10 when handling the transparent adhesive sheet X2 with release material, and appropriate releasability of the release liner R1 and dicing tape 20 from the transparent adhesive sheet 10.
[0112] 4 to 7 show a bonding method using a transparent adhesive sheet X2 with a release material. This bonding method includes the following lamination step, singulation step, temporary fixing step, and bonding step.
[0113] In the lamination step, the release liner R1 is peeled off from the transparent adhesive sheet X2 with a release material to expose the transparent adhesive sheet 10, and then the workpiece W is laminated onto the transparent adhesive sheet 10 as shown in Fig. 4. The workpiece W has a first surface Wa that is the side to be laminated to the transparent adhesive sheet 10, and a second surface Wb on the opposite side. The workpiece W has multiple optical sensors built in, each having a detection surface on the first surface Wa side.
[0114] In the singulation process, the workpiece W on the transparent adhesive sheet 10 is cut by a dicing blade of a dicing device to singulate the workpiece W as shown in FIG. 5 (the cut portions are shown by thick lines in FIG. 5). Specifically, in this process, the workpiece W is singulated into optical sensors 1, and the transparent adhesive sheet 10 is cut into small pieces. This results in an optical sensor 1 with the transparent adhesive sheet 10 or the adhesive layer 11 derived therefrom on the detection surface 1a side, i.e., an optical sensor 1 with the adhesive layer 11.
[0115] When the adhesive layer 22 of the dicing tape 20 contains a radiation-curable adhesive, after the above-mentioned dicing step, the adhesive layer 22 may be irradiated with radiation such as ultraviolet light from the side of the substrate 21 to reduce the adhesive strength of the adhesive layer 22. The irradiation dose is, for example, 50 to 500 mJ / cm. 2 It is.
[0116] In the temporary fixing process, the optical sensor 1 with the adhesive layer 11 is picked up from the dicing tape 20, and then, as shown in Figure 6, the optical sensor 1 with the adhesive layer 11 is pressed against the transparent cover member 2 via its adhesive layer 11 side to temporarily fix it.
[0117] In the bonding process, as shown in FIG. 7, the adhesive layer 11 interposed between the temporarily fixed optical sensor 1 and the transparent cover member 2 is thermally cured to bond the detection surface 1a of the optical sensor 1 and the transparent cover member 2.
[0118] In this manner, the optical sensor 1 and the transparent cover member 2 can be joined together using the transparent adhesive sheet X2 with a release material.
[0119] The transparent adhesive sheet X2 with a release material includes a transparent adhesive sheet 10, similar to the transparent adhesive sheet X1 with a release material. As described above with respect to the embodiment of the transparent adhesive sheet X1 with a release material, the transparent adhesive sheet 10 is suitable for manufacturing an optical sensor-mounted device with a high yield as a bonding material between the detection surface 1a of the optical sensor 1 and the transparent cover member 2, and is suitable for ensuring the sensor detection sensitivity. In addition, in the above-mentioned bonding method performed using the transparent adhesive sheet X2 with a release material, the transparent adhesive sheet 10 or a small member piece with the adhesive layer 11 derived therefrom (in this embodiment, the optical sensor 1 with the adhesive layer 11) can be efficiently obtained. Therefore, this bonding method is suitable for improving the efficiency of the work and process of bonding between bonding objects. EXAMPLES
[0120] Example 1 An adhesive composition with a solids concentration of 20% by mass was prepared by adding and mixing 90 parts by mass of acrylic resin A1 (product name "Teisan Resin SG-80H", weight average molecular weight 350,000, glass transition temperature Tg 11°C, manufactured by Nagase ChemteX Corporation), 7 parts by mass of inorganic filler (product name "YA010C", spherical silica particles, average particle diameter 10 nm, manufactured by Admatechs Co., Ltd.), 0.27 parts by mass of curing agent (product name "Curesol 2MZ", imidazole-based curing agent, Shikoku Chemical Industry Co., Ltd.), and 0.27 parts by mass of antioxidant (product name "Adeka STAB PEP-8", phosphorus-based antioxidant, manufactured by ADEKA Corporation) to methyl ethyl ketone. Next, an adhesive composition was applied to the silicone release-treated surface of a polyethylene terephthalate (PET) film (trade name "Diafoil MRF", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) as a first release material having a silicone release-treated surface using an applicator to form an adhesive composition layer. Next, this composition layer was heated and dried at 130° C. for 2 minutes to prepare a transparent adhesive sheet having a thickness of 20 μm on the PET film. Then, the silicone release-treated surface side of a PET film (trade name "Diafoil MRA", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) as a second release material having a silicone release-treated surface was attached to the transparent adhesive sheet under a temperature condition of 60° C. In this manner, a transparent adhesive sheet with a release material of Example 1 having a laminated structure of a PET film (first release material) having a thickness of 38 μm, a PET film (second release material) having a thickness of 25 μm, and a transparent adhesive sheet having a thickness of 20 μm between them was prepared.
[0121] Example 2 <Preparation of dicing tape> In a reaction vessel equipped with a cooling tube, a nitrogen introduction tube, a thermometer, and a stirrer, a mixture containing 120 parts by mass of 2-ethylhexyl acrylate, 17 parts by mass of 2-hydroxyethyl acrylate, 0.4 parts by mass of benzoyl peroxide as a polymerization initiator, and 80 parts by mass of toluene as a polymerization solvent was stirred under a nitrogen atmosphere at 60°C for 10 hours (polymerization reaction). This resulted in a polymer solution containing an acrylic polymer P1. Next, a mixture containing the polymer solution containing the acrylic polymer P1, 2-methacryloyloxyethyl isocyanate (MOI), and dibutyltin dilaurate as an addition reaction catalyst was stirred under an air atmosphere at 50°C for 60 hours (addition reaction). In the reaction solution, the amount of MOI blended was 1.4 parts by mass relative to 1100 parts by mass of the acrylic polymer P1, and the amount of dibutyltin dilaurate blended was 0.1 parts by mass relative to 1100 parts by mass of the acrylic polymer P1. This addition reaction gave a polymer solution containing an acrylic polymer P2 having a methacryloyl group in the side chain. Next, 1.1 parts by mass of a polyisocyanate compound (trade name "Coronate L", manufactured by Tosoh Corporation) and 3 parts by mass of a photopolymerization initiator (trade name "Irgacure 184", manufactured by BASF) were added to the polymer solution relative to 100 parts by mass of the acrylic polymer P2, and mixed. Then, toluene was added to the mixture to dilute it so that the viscosity of the mixture at room temperature was 500 mPa·s, and a pressure-sensitive adhesive composition was obtained. Next, the pressure-sensitive adhesive composition was applied using an applicator to the silicone release-treated surface of a PET film (thickness 38 μm) having a surface treated with a silicone release treatment to form a pressure-sensitive adhesive composition layer. Next, this composition layer was heated and dried at 120 ° C for 2 minutes, and a pressure-sensitive adhesive layer having a thickness of 30 μm was formed on the PET film. Next, a laminator was used to attach an ethylene-vinyl acetate copolymer (EVA) substrate (product name "Fanclair NRB#80", thickness 80 μm, manufactured by Gunze Co., Ltd.) to the exposed surface of the adhesive layer at room temperature. In this manner, a dicing tape was produced.
[0122] <Preparation of transparent adhesive sheet with release material> An adhesive composition with a solids concentration of 20% by mass was prepared by adding and mixing 90 parts by mass of acrylic resin A1 (trade name "Teisan Resin SG-80H", weight average molecular weight 350,000, glass transition temperature Tg 11°C, manufactured by Nagase ChemteX Corporation), 65 parts by mass of inorganic filler (trade name "MEK-ST-ZL", spherical silica particles, particle diameter 70 to 100 nm, manufactured by Nissan Chemical Industries, Ltd.), 0.9 parts by mass of curing agent (trade name "Curesol 2MZ", imidazole-based curing agent, Shikoku Chemical Industries, Ltd.), and 0.9 parts by mass of antioxidant (trade name "Adeka STAB PEP-8", phosphorus-based antioxidant, manufactured by ADEKA Corporation) to methyl ethyl ketone. Next, the adhesive composition was applied to the silicone release-treated surface of a PET film (product name "Diafoil MRA", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) as a first release material having a surface treated with silicone release treatment, using an applicator to form an adhesive composition layer. Next, this composition layer was heated and dried at 130° C. for 2 minutes to prepare a transparent adhesive sheet having a thickness of 20 μm on the PET film. Then, the transparent adhesive sheet with a release material of Example 2 was prepared in the same manner as the transparent adhesive sheet with a release material of Example 1, except that the above-mentioned dicing tape was used instead of the above-mentioned PET film having a thickness of 25 μm as the second release material. Specifically, after peeling the PET film from the dicing tape prepared as described above, the adhesive layer side of the dicing tape was attached to the transparent adhesive sheet with a thickness of 20 μm on the PET film (first release material) under a temperature condition of 60° C. In this manner, a transparent adhesive sheet with release material of Example 2 was produced, having a laminated structure of a 38 μm thick PET film (first release material), a 110 μm thick dicing tape (second release material), and a 20 μm thick transparent adhesive sheet between them.
[0123] Example 3 An adhesive composition with a solids concentration of 20% by mass was prepared by adding and mixing 93 parts by mass of an acrylic resin solution (product name "PARACRON EG-2201M", solids concentration of 60% by mass, weight average molecular weight of 100,000, glass transition temperature Tg of -40°C, manufactured by Negami Chemical Industrial Co., Ltd.) in terms of the mass of the acrylic resin, 41 parts by mass of an inorganic filler (product name "YA010C", spherical silica particles, average particle diameter of 10 nm, manufactured by Admatechs Co., Ltd.), 0.4 parts by mass of a curing agent (product name "Curesol 2MZ", imidazole-based curing agent, Shikoku Chemical Industry Co., Ltd.), and 0.5 parts by mass of an antioxidant (product name "ADEKA STAB PEP-8", phosphorus-based antioxidant, manufactured by ADEKA Corporation) to methyl ethyl ketone. Next, the adhesive composition was applied to the silicone release-treated surface of a PET film (trade name "Diafoil MRA", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) as a first release material having a surface treated with silicone release treatment, using an applicator to form an adhesive composition layer. Next, this composition layer was heated and dried at 130° C. for 2 minutes to prepare a transparent adhesive sheet having a thickness of 20 μm on the PET film. Then, the silicone release-treated surface side of a PET film (trade name "Diafoil MRF", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) as a second release material having a surface treated with silicone release treatment was attached to the transparent adhesive sheet under a temperature condition of 60° C. In this manner, a transparent adhesive sheet with a release material of Example 3 having a laminated structure of a PET film (first release material) having a thickness of 38 μm, a PET film (second release material) having a thickness of 25 μm, and a transparent adhesive sheet having a thickness of 20 μm between them was prepared.
[0124] Comparative Example 1 90 parts by mass of acrylic resin A2 (trade name "Teisan Resin WS-023 EK30", weight average molecular weight 500,000, glass transition temperature Tg -10 ° C., Nagase Chemtex Corporation), 3 parts by mass of phenolic resin (trade name "MEH-7851H", Meiwa Kasei Co., Ltd.), 52 parts by mass of epoxy resin (trade name "KI-3000", Tohto Kasei Co., Ltd.), 60 parts by mass of inorganic filler (trade name "SO-25R", silica particles, average particle size 500 nm, Admatechs Co., Ltd.), and methyl ethyl ketone were added and mixed to prepare an adhesive composition with a solid content concentration of 20% by mass. Next, the adhesive composition was applied using an applicator onto the silicone release-treated surface of a polyethylene terephthalate (PET) film (trade name "Cerapeel WZ", thickness 20 μm, Toray Film Processing Co., Ltd.) as a first release material having a surface treated with silicone release treatment to form an adhesive composition layer. Next, this composition layer was heated and dried at 130°C for 2 minutes to prepare a transparent adhesive sheet having a thickness of 20 μm on the PET film. Then, the silicone release-treated surface of a PET film (trade name "Diafoil MRF", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) as a second release material having a surface treated with silicone release treatment was attached to the transparent adhesive sheet under a temperature condition of 60°C. In this manner, a transparent adhesive sheet with a release material of Comparative Example 1 having a laminated structure of a PET film having a thickness of 20 μm (first release material), a PET film having a thickness of 25 μm (second release material), and a transparent adhesive sheet having a thickness of 20 μm between them was prepared.
[0125] <Transmittance measurement> For the transparent adhesive sheets with a release material of Examples 1 to 3 and Comparative Example 1, the transmittance before heat curing, the transmittance in a heat cured state, the transmittance after a predetermined moisture absorption test in a heat cured state, and the transmittance after a predetermined heating test in a heat cured state were examined. Each heat curing of the transparent adhesive sheet was performed under heating conditions of 150°C for 1 hour. In the moisture absorption test, the transparent adhesive sheet after heat curing was placed in an environment of 30°C and relative humidity of 70% for 200 hours. In the heating test, the transparent adhesive sheet after heat curing was placed under heating conditions of 260°C for 5 minutes. In each transmittance measurement, a sample piece cut out from the transparent adhesive sheet (thickness 20 μm) was used to measure the total light transmittance spectrum in the wavelength range of 300 to 1300 nm using an ultraviolet-visible-near infrared spectrophotometer (product name "V-670DS", manufactured by JASCO Corporation) and an integrating sphere unit. The minimum transmittance of the transparent adhesive sheet after heat curing in the wavelength range of 450 to 1200 nm is set as transmittance T1 (%), the transmittance of the transparent adhesive sheet in the heat cured state at 450 nm is set as transmittance T2 (%), the transmittance of the transparent adhesive sheet in the heat cured state after the moisture absorption test is set as transmittance T3 (%), and the transmittance of the transparent adhesive sheet in the heat cured state after the heating test is set as transmittance T4 (%), all of which are shown in Table 1. Table 1 also shows the values of T3 / T2 and T4 / T2.
[0126] <Viscosity measurement> The viscosity of the transparent adhesive sheets with release liner of Examples 1 to 3 and Comparative Example 1 was measured using a dynamic viscoelasticity measuring device (product name "HAAKE MARS III", manufactured by Thermo Fisher Scientific). The sample pieces to be measured were prepared by forming a laminate in which multiple transparent adhesive sheets were laminated to a thickness of 200 μm, and then cutting the laminate into a disk shape with a diameter of 8 mm. In this measurement, the measurement temperature range was 80°C to 180°C, the heating rate was 5°C / min, and the frequency was 1 Hz.
[0127] Storage Modulus The storage modulus of the transparent adhesive sheets with release liner of Examples 1 to 3 and Comparative Example 1 was examined by dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (product name "RSA-III", manufactured by TA Instruments). The sample pieces to be subjected to the dynamic viscoelasticity measurement were prepared by forming a laminate in which a plurality of transparent adhesive sheets were laminated to a thickness of 200 μm, cutting out a size of 10 mm wide x 40 mm long from the laminate, and then heat curing the laminate by heating at 150°C for 1 hour. In addition, in this measurement, the initial chuck distance of the chucks for holding the sample pieces was 22.5 mm, the measurement mode was a tension mode, the measurement temperature range was -30°C to 250°C, the frequency was 1 Hz, the dynamic strain was 0.005%, and the heating rate was 10°C / min. The storage modulus (MPa) at 250°C obtained is shown in Table 1.
[0128] [Weight reduction rate] The transparent adhesive sheets with release liner of Examples 1 to 3 and Comparative Example 1 were examined for weight loss at 300°C. A sample of about 10 mg was cut out from the transparent adhesive sheet, and the weight loss during the heating process was measured for this sample using a simultaneous differential thermal and thermogravimetric analyzer (product name "Thermo plus TG8120", manufactured by Rigaku Corporation). This measurement was performed in a nitrogen atmosphere, with the temperature increased from 23°C, which was the reference weight temperature, to 300°C at a heating rate of 10°C / min. The weight loss rate (%) of the sample from 23°C (reference weight) to 300°C is shown in Table 1.
[0129] [Adhesion to glass] The adhesive strength of the transparent adhesive sheet with release material of Examples 1 to 3 and Comparative Example 1 to a flat glass surface was examined. First, a backing tape (product name "BT-315", manufactured by Nitto Denko Corporation) was attached to one side of the transparent adhesive sheet, and then a sample piece (width 10 mm x length 150 mm) was cut out from the transparent adhesive sheet with the backing tape. Next, after confirming that the surface temperature of the glass plate placed on a hot plate set at 60°C was 60°C, the surface of the glass plate (flat glass surface) and the exposed surface of the transparent adhesive sheet in the sample piece were attached to each other. This attachment was performed by a pressure bonding operation in which a 2 kg hand roller was moved back and forth once. After this attachment, the sheet was left to stand on a hot plate for 2 minutes, and then left to stand at room temperature for 20 minutes. A peel test was then conducted using a tensile tester (product name "Autograph AGS-J", manufactured by Shimadzu Corporation) to peel the sample piece from the glass plate at 23°C, a peel angle of 180°, and a peel speed of 300 mm / min, and the 180° peel adhesive strength (N / 10 mm) of the transparent adhesive sheet against the flat glass surface at 23°C was measured. The results are shown in Table 1.
[0130] [Shear adhesive strength to glass] The shear adhesive strength of the transparent adhesive sheet with a release material of Examples 1 to 3 and Comparative Example 1 against a flat glass surface was examined. The transparent adhesive sheets of Examples 1 and 3 and Comparative Example 1 were attached to a dicing tape to form a transparent adhesive sheet with a dicing tape, and the transparent adhesive sheet with a release material of Example 2 was attached to a transparent adhesive sheet with a dicing tape by peeling off the first release material. Each transparent adhesive sheet with a dicing tape was used as follows. First, a silicon wafer (thickness 500 μm) was attached to the transparent adhesive sheet of the transparent adhesive sheet with a dicing tape. In the attachment, a laminator was used, the attachment speed was set to 10 mm / sec, the temperature condition was set to 60° C., and the pressure condition was set to 0.15 MPa. Next, the silicon wafer on the transparent adhesive sheet with a dicing tape was divided into chips (5 mm×5 mm) by blade dicing using a dicing device (product name “DFD6361”, manufactured by Disco Corporation). As a result, a chip with an adhesive layer derived from the transparent adhesive sheet was obtained. The chip with the adhesive layer was pressed against a glass plate via the adhesive layer side (temporary fixation). In this temporary fixation, the pressing temperature was 120°C, the pressing load was 0.1 MPa, and the pressing time was 2 seconds. Next, the adhesive layer interposed between the glass plate and the chip was thermally cured by heating at 150°C for 1 hour, and the glass plate and the chip were bonded by the adhesive layer. In this way, a sample for measuring the shear adhesive strength to glass was prepared. Then, the shear adhesive strength F1 (MPa) of the sample was measured using a bonding strength tester (trade name "Dage4000", manufactured by Nordson). In addition, the sample prepared as described above was subjected to a moisture absorption test under conditions of 40°C, relative humidity 95%, and 120 hours, and then the shear adhesive strength F2 (MPa) was measured using a bonding strength tester (trade name "Dage4000", manufactured by Nordson). In each measurement, the measurement temperature was 23° C., the shear rate was 30 mm / min, and the maximum stress value obtained was taken as the shear adhesive strength (MPa). These results and the value of F2 / F1 are shown in Table 1.
[0131] Refractive index measurement The refractive index at 633 nm after thermal curing was examined for the transparent adhesive sheets with release material of Examples 1 to 3 and Comparative Example 1. The transparent adhesive sheets were thermally cured under heating conditions of 150°C for 1 hour. The refractive index was measured using a refractive index measuring device (product name "Prism Coupler Model 2010 / M", manufactured by Metricon). The measurement results are shown in Table 1.
[0132] [Peel adhesion of release material] The peel adhesion of the first release material to the transparent adhesive sheet was examined for the transparent adhesive sheet with the release material of Examples 1 to 3 and Comparative Example 1. Specifically, the second release material was first peeled off from the transparent adhesive sheet with the release material, and then a backing tape (product name "BT-315", manufactured by Nitto Denko Corporation) was attached to the exposed transparent adhesive sheet, and a sample piece (width 100 mm x length 60 mm) was cut out from the transparent adhesive sheet with the backing tape. Then, a peel test was performed to peel the first release material from the transparent adhesive sheet under conditions of 23°C, a peel angle of 180°, and a peel speed of 300 mm / min using a tensile tester (product name "Autograph AGS-J", manufactured by Shimadzu Corporation), and the 180° peel adhesion (N / 100 mm) of the first release material to the transparent adhesive sheet at 23°C was measured. After the first release material was peeled off from the transparent adhesive sheet with the release material, a backing tape (product name "BT-315", manufactured by Nitto Denko Corporation) was attached to the exposed transparent adhesive sheet, and a sample piece (width 100 mm x length 60 mm) was cut out from the transparent adhesive sheet with the backing tape. Then, a peel test was performed to peel the second release material from the transparent adhesive sheet under conditions of 23°C, a peel angle of 180°, and a peel speed of 300 mm / min using a tensile tester (product name "Autograph AGS-J", manufactured by Shimadzu Corporation), and the 180° peel adhesion strength (N / 100 mm) of the second release material against the transparent adhesive sheet at 23°C was measured. The peel adhesion strength P1 of the first release material, the peel adhesion strength P2 of the second release material, and the value of P1 / P2 are shown in Table 1.
[0133] [Peel test] A peel test was carried out on the transparent adhesive sheets with a release liner of Examples 1 to 3 and Comparative Example 1 as follows. The transparent adhesive sheets with a release liner used in the peel test had a size of 10 cm x 10 cm. A 10 mm wide backing tape (product name "BT-315", manufactured by Nitto Denko Corporation) was attached to one of the corners of the exposed surface of the first release liner of this transparent adhesive sheet with a release liner, with an application area of 12.5 mm. 2 The first release material was then peeled off from the transparent adhesive sheet by pulling the backing tape at an angle of 180° to the transparent adhesive sheet. If the first release material could be peeled off from the transparent adhesive sheet without peeling between the transparent adhesive sheet and the second release material during the peeling process, it was rated as "good", and if peeling occurred between the transparent adhesive sheet and the second release material, it was rated as "poor". The evaluation results are shown in Table 1.
[0134] [Heat test after moisture absorption] The transparent adhesive sheets with release material of Examples 1 to 3 and Comparative Example 1 were subjected to a post-moisture absorption heating test as follows. First, a transparent adhesive sheet was attached to the 9.5 mm square plane of a 9.5 mm square silicon mirror chip to prepare a chip with an adhesive layer. The temperature during attachment was 60°C. Next, the chip with the adhesive layer was pressed against a glass plate via the adhesive layer side (temporarily fixed). In this temporary fixing, the pressing temperature was 120°C, the pressing load was 0.1 MPa, and the pressing time was 2 seconds. Next, the adhesive layer interposed between the glass plate and the chip was thermally cured under heating conditions of 150°C, a pressure of 0.7 MPa, and 1 hour, and the glass plate and the chip were bonded by the adhesive layer. In this way, 9 bonded samples were prepared for each transparent adhesive sheet. Next, the bonded samples were subjected to a moisture absorption treatment under conditions of a temperature of 30°C, a humidity of 60% RH, and a time of 72 hours. Next, the bonded samples were passed through an IR reflow furnace set to maintain a temperature of 260°C or higher for 10 seconds. The bonded samples were then examined to see whether peeling had occurred at the interface between the transparent adhesive sheet and the glass plate. The nine bonded samples were rated as "good" when no peeling occurred at the interface between the transparent adhesive sheet and the glass plate, and were rated as "poor" when peeling occurred at the interface between the transparent adhesive sheet and the glass plate in at least one of the nine bonded samples. The evaluation results are shown in Table 1.
[0135] [Table 1]
[0136] In summary, the configuration of the present invention and variations thereof are listed below as appendices.
[0137] (Appendix 1) A transparent adhesive sheet that is thermosetting and has a transmittance of 85% or more, preferably 87% or more, and more preferably 90% or more in a wavelength range of 450 to 1200 nm when heat-cured by heating at 150°C for 1 hour. (Appendix 2) The transparent adhesive sheet according to claim 1, wherein in the heat-cured state, the ratio of the transmittance at a wavelength of 450 nm after the moisture absorption test under conditions of 30°C, 70% relative humidity, and 200 hours to the transmittance at a wavelength of 450 nm before the moisture absorption test is 0.9 or more, preferably 0.92 or more, and more preferably 0.94 or more. (Appendix 3) A transparent adhesive sheet according to appendix 1 or 2, in which in the heat-cured state, the ratio of the transmittance at a wavelength of 450 nm after the heating test at 260°C for 5 minutes to the transmittance at a wavelength of 450 nm before the heating test is 0.9 or more, preferably 0.92 or more, and more preferably 0.94 or more. (Appendix 4) 4. The transparent adhesive sheet according to any one of claims 1 to 3, having a viscosity at 120°C of 1 to 30 kPa·s, preferably 3 to 30 kPa·s, more preferably 4 to 27 kPa·s, and more preferably 5 to 25 kPa·s. (Appendix 5) 5. The transparent adhesive sheet according to any one of claims 1 to 4, wherein the storage modulus at 250° C. in the heat cured state is from 0.5 to 50 MPa, preferably from 0.6 to 45 MPa, and more preferably from 0.7 to 40 MPa. (Appendix 6) A transparent adhesive sheet described in any one of Appendices 1 to 5, in which in the heat-cured state, the weight loss rate at 300°C in thermogravimetry under conditions of a nitrogen atmosphere, a heating rate of 10°C / min, and a heating range of 23 to 300°C is 1.5% or less, preferably 1.2% or less. (Appendix 7) A transparent adhesive sheet according to any one of Appendices 1 to 6, which exhibits a peel adhesion strength of 1 N / 10 mm or more, preferably 1.5 N / 10 mm or more, against a flat glass surface in a peel test under conditions of 23°C, a peel angle of 180°, and a peel speed of 30 mm / min. (Appendix 8) A transparent adhesive sheet according to any one of Appendices 1 to 7, in which the ratio of the glass shear adhesive strength after a moisture absorption test under conditions of 40°C, relative humidity 95%, and 120 hours, when the sheet is heated at 150°C for 1 hour and then adhered to a flat glass surface, to the glass shear adhesive strength before the moisture absorption test, is 0.6 or more, preferably 0.7 or more, and more preferably 0.75 or more. (Appendix 9) 9. The transparent adhesive sheet according to any one of claims 1 to 8, wherein the refractive index at a wavelength of 633 nm in the heat-cured state is 1.4 to 1.5, and preferably 1.42 to 1.48. (Appendix 10) 10. A transparent adhesive sheet according to any one of claims 1 to 9, comprising an acrylic resin. (Appendix 11) 11. The transparent adhesive sheet according to claim 10, wherein the acrylic resin has a nitrile group. (Appendix 12) 12. The transparent adhesive sheet according to claim 10 or 11, wherein the acrylic resin has an epoxy group. (Appendix 13) 13. The transparent adhesive sheet according to any one of claims 10 to 12, wherein the average molecular weight of the acrylic resin is 400,000 or less, and preferably 350,000 or less. (Appendix 14) 14. The transparent adhesive sheet according to any one of claims 10 to 13, wherein the proportion of the acrylic resin in the organic components contained is 95% by mass or more, and preferably 97% by mass or more. (Appendix 15) 15. A transparent adhesive sheet according to any one of claims 1 to 14, which does not contain or substantially does not contain an epoxy resin and / or a phenol resin. (Appendix 16) 16. The transparent adhesive sheet according to any one of claims 1 to 15, comprising a filler having an average particle size of 5 to 100 nm. (Appendix 17) 17. The transparent adhesive sheet according to claim 16, wherein the filler content is 5 to 45% by mass, preferably 6 to 40% by mass, and more preferably 7 to 35% by mass. (Appendix 18) 18. A transparent adhesive sheet according to any one of claims 1 to 17, comprising a phosphorus-based antioxidant. (Appendix 19) 19. The transparent adhesive sheet according to claim 18, wherein the content of the phosphorus-based antioxidant is 0.1 to 2% by mass, and preferably 0.3 to 1.5% by mass. (Appendix 20) 20. A transparent adhesive sheet according to any one of claims 1 to 19, containing an imidazole-based curing agent. (Appendix 21) 21. The transparent adhesive sheet according to claim 20, wherein the content of the imidazole curing agent is 0.1 to 2% by mass, and preferably 0.2 to 1.5% by mass. (Appendix 22) A transparent adhesive sheet with a release material, having a laminated structure including a first release material, a second release material, and a transparent adhesive sheet described in any one of Appendices 1 to 21 between these release materials. (Appendix 23) The first release material has a thickness of 38 μm or more, The second release material has a thickness of 25 μm or more, 23. The transparent adhesive sheet with a release material according to claim 22, wherein the ratio of the thickness of the first release material to the thickness of the second release material is 0.2 to 1.8, preferably 0.22 to 1.55, and more preferably 0.3 to 1.6. (Appendix 24) the first release material exhibits a first peel adhesion strength of 0.01 N / 100 mm or more, preferably 0.015 N / 100 mm or more, in a peel test under conditions of 100° C., a peel angle of 180°, and a peel speed of 300 mm / min, relative to the transparent adhesive sheet; A transparent adhesive sheet with a release material described in Appendix 22 or 23, wherein the second release material exhibits a second peel adhesion force of 0.04 N / 100 mm or more when tested against the transparent adhesive sheet at 100°C, a peel angle of 180°, and a peel speed of 300 mm / min. (Appendix 25) 25. The transparent adhesive sheet with a release material according to claim 24, wherein the ratio of the first peel adhesion strength to the second peel adhesion strength is 0.01 to 0.75, and preferably 0.02 to 0.7. (Appendix 26) the second release material is a dicing tape having a laminated structure including a base material and a pressure-sensitive adhesive layer, 26. A transparent adhesive sheet with a release material according to any one of claims 22 to 25, wherein the transparent adhesive sheet is releasably adhered to the pressure-sensitive adhesive layer of the dicing tape. (Appendix 27) 27. The transparent adhesive sheet with a release material according to claim 26, wherein the pressure-sensitive adhesive layer contains an acrylic resin having a 2-ethylhexyl group. (Appendix 28) 28. The transparent adhesive sheet with a release material according to claim 26 or 27, wherein the pressure-sensitive adhesive layer has a thickness of 5 to 40 μm, and preferably 10 to 30 μm. (Appendix 29) A bonding method for bonding a glass member and another member using the transparent adhesive sheet according to any one of claims 1 to 21. (Appendix 30) A bonding method for bonding a transparent resin member having a transmittance of 80% or more at a wavelength of 500 nm to another member by using the transparent adhesive sheet according to any one of claims 1 to 21. (Appendix 31) A step of attaching a transparent adhesive sheet according to any one of claims 1 to 21 to a member; A step of singulating the component together with the transparent adhesive sheet to obtain a component piece with the transparent adhesive sheet; and a step of bonding the component piece with the transparent adhesive sheet to another component via the transparent adhesive sheet. [Explanation of symbols]
[0138] 1 Optical Sensor 1a Detection surface 2 Transparent cover material X1,X2 Transparent adhesive sheet with release agent 10 Transparent adhesive sheet 11 Adhesive layer R1, R2 Release liner 20 Dicing tape 21 Base material 22 Adhesive layer Double work
Claims
1. It has a thermosetting property, and when it is heat-cured by heating at 150° C. for 1 hour, the minimum transmittance in the wavelength range of 450 to 1200 nm is 85% or more, A transparent adhesive sheet comprising an acrylic resin, the proportion of the acrylic resin in organic components being 97 mass % or more.
2. 2. The transparent adhesive sheet according to claim 1, wherein in the heat-cured state, the ratio of the transmittance at a wavelength of 450 nm after the moisture absorption test under conditions of 30° C., relative humidity of 70%, and 200 hours to the transmittance at a wavelength of 450 nm before the moisture absorption test is 0.9 or more.
3. 3. The transparent adhesive sheet according to claim 1, wherein in the heat-cured state, the ratio of the transmittance at a wavelength of 450 nm after the heating test at 260°C for 5 minutes to the transmittance at a wavelength of 450 nm before the heating test is 0.9 or more.
4. 4. The transparent adhesive sheet according to claim 1, having a viscosity at 120° C. of 1 to 30 kPa·s.
5. 5. The transparent adhesive sheet according to claim 1, wherein the storage modulus at 250° C. in the heat-cured state is 0.5 to 50 MPa.
6. The transparent adhesive sheet according to any one of claims 1 to 5, wherein in the heat-cured state, the weight loss rate at 300°C is 1.5% or less when measured by thermogravimetry under conditions of a nitrogen atmosphere, a heating rate of 10°C / min, and a heating range of 23 to 300°C.
7. 7. The transparent adhesive sheet according to claim 1, which exhibits a peel adhesion strength of 1 N / 10 mm or more against a flat glass surface in a peel test under conditions of 23° C., a peel angle of 180°, and a peel speed of 30 mm / min.
8. 8. The transparent adhesive sheet according to claim 1, wherein the ratio of the glass shear adhesive strength after a moisture absorption test under conditions of 40°C, relative humidity 95%, and 120 hours to the glass shear adhesive strength before the moisture absorption test, when the sheet is heated at 150°C for 1 hour and then adhered to a flat glass surface, is 0.6 or more.
9. 9. The transparent adhesive sheet according to claim 1, wherein the refractive index at a wavelength of 633 nm in the heat-cured state is 1.4 to 1.
5.
10. A transparent adhesive sheet with a release material, having a laminated structure including a first release material, a second release material, and the transparent adhesive sheet according to claim 1 between these release materials.
11. The first release material has a thickness of 38 μm or more; The second release material has a thickness of 25 μm or more, 11. The transparent adhesive sheet with a release material according to claim 10, wherein a ratio of a thickness of the first release material to a thickness of the second release material is 0.2 to 1.
8.
12. the first release material exhibits a first peel adhesion strength of 0.01 N / 100 mm or more in a peel test under conditions of 100° C., a peel angle of 180°, and a peel speed of 300 mm / min against the transparent adhesive sheet; 12. The transparent adhesive sheet with release material according to claim 10 or 11, wherein the second release material exhibits a second peel adhesion force of 0.04 N / 100 mm or more against the transparent adhesive sheet in a peel test under conditions of 100° C., a peel angle of 180°, and a peel speed of 300 mm / min.
13. 13. The transparent adhesive sheet with a release material according to claim 12, wherein a ratio of the first peel adhesion strength to the second peel adhesion strength is 0.01 to 0.
75.
14. the second release material is a dicing tape having a laminated structure including a base material and a pressure-sensitive adhesive layer, The transparent adhesive sheet with a release material according to claim 10 , wherein the transparent adhesive sheet is releasably adhered to the pressure-sensitive adhesive layer of the dicing tape.
Citation Information
Patent Citations
Adhesive composition for optical waveguide, and adhesive film for optical waveguides using the same, and optical device using these
JP2008260908A
Thermosetting type adhesive tape or sheet
JP2009263400A
Adhesive sheet for sticking wafer and processing method of wafer using the same
JP2012015236A
Die-bonding film and use thereof
JP2012191046A
Postcure tape and method for joining joint member
JP2014028911A